Molybdenum‐Incorporated O3‐type Sodium Layered Oxide Cathodes for High‐Performance Sodium‐Ion Batteries - Buzaina Moossa (17337883) (2023)
Transition metal layered oxide materials with a general formula NaxMO2 (M = Ni, Mn, Co, Fe) are widely researched with various possible electrode configurations. Herein, O3‐type NaNi(1−x)/2Mn(1−x)/2MoxO2 (x = 0, 0.05,0.1) layered oxide cathode materials are synthesized by solid‐state reaction method, and its structural, thermal, and electrochemical performance in sodium ion battery is investigated. The structural analysis reveals that a single phase highly crystalline O3‐type cathode material with an irregular particle shape is formed. The introduction of molybdenum improves the thermal stability of cathode materials, which can be attributed to the improved TMO2 layers that provide stability to the material. The addition of Mo to Na‐layered oxide cathode materials enhances electrochemical performance. The developed cathode materials, the NaNi0.475Mn0.475Mo0.05O2, exhibit excellent specific discharge capacity (≈154 mAh g−1) at C/20 rate, (an increase of ≈20% when compared to the NaNi0.5Mn0.5O2) which can be attributed to the increased capacitance effect by the addition of Mo. The electrochemical impedance spectroscopy study reveals that the diffusion of Na+ into/from the host structure is rapid during the first cycle and then gradually reduces with subsequent cycling due to the formation of the solid electrolyte interface layer, which hinders Na+ migration. This has a potential effect on the improved electrochemical performance of the material. Other Information Published in: Energy Technology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ente.202300437